HUBUNGAN PENGETAHUAN REMAJA DENGAN SIKAP DALAM PENANGANAN NON FARMAKOLOGI (SENAM DISMENORE) UNTUK MENGURANGI NYERI DISMENORE DI SMA SEKOLAH RAKYAT BEKASI UTARA - Umi Salamah; Siti Muslima W Udi (Jurnal Ilmiah Kebidanan Imelda, 2025)
Exercise for dysmenorrhea is a method of relaxation that may release endorphins, which are substances that the brain and spinal cord can create 90% of the population, or 1,769,425 persons, had severe dysmenorrhea in 2016, based on data from the WHO. Comparing Indonesia to other nations, the country's dysmenorrhea rate is equally high. In Indonesia, between 45 and 95 percent of women of working age have dysmenorrhea, with primary dysmenorrhea accounting for 72.89% of cases and secondary dysmenorrhea for 21.11%. Ascertain the connection between teenage attitudes and understanding about non-pharmacological therapy (dysmenorrhea exercise) and its ability to alleviate dysmenorrhea discomfort at Bekasi Regency People's High School in 2022. The cross-sectional approach and analytical research methodology. The sample for this study consists of 90 adolescent girls, and it utilises both primary and secondary data. A survey was employed as the research tool. The study was conducted at Bekasi People's High School. Using a population of 103, the sampling method was purposive random sampling. Both univariate and bivariate analysis were employed. According to the study's findings, the most deficient level of knowledge was 35 (39%), the most negative attitude was 51 (56.7%), the most unsupportive family support was 52 (57.8%), the most favourable environment was 55 (61.1%), and the most direct source of information was 47 (52.2%). Conclusion: In 2022, female high school students at Bekasi People's School showed a strong correlation between their knowledge and attitudes about the Dysmenorrhea Exercise (P value = 0.033 > a=0.05).